Biocompatible materials and methods of preparation and use thereof

By using polymer compositions with high intrinsic viscosity and low intrinsic viscosity, a hydrogel with low mechanical strength and adjustable mechanical properties is formed, which solves the problem of difficult control of hydrogel properties in traditional techniques, and achieves hydrogel preparation suitable for drug packaging.

CN115443292BActive Publication Date: 2025-02-28PLERYON THERAPEUTICS (SHENZHEN) LTD
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202180029419.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2020-04-23
Filing Date
2021-04-22
Publication Date
2025-02-28
Estimated Expiration
2041-04-22

AI Technical Summary

Technical Problem

It is difficult to effectively prepare low mechanical strength hydrogels with the desired properties in the prior art, and traditional crosslinking agents may be toxic to the human body.

Method used

Using a composition comprising a first polymer with a high intrinsic viscosity and a second polymer with a low intrinsic viscosity, the hydrogel is formed by reaction and the mechanical properties of the hydrogel are adjusted under different conditions.

Benefits of technology

The preparation of hydrogels with relatively low G’, high G” ratios and high yield strains is achieved, and has low viscosity at high shear rates, suitable as pharmaceutical packaging materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure GDA0003897466620000211
    Figure GDA0003897466620000211
  • Figure GDA0003897466620000221
    Figure GDA0003897466620000221
  • Figure GDA0003897466620000222
    Figure GDA0003897466620000222
Patent Text Reader

Abstract

The present disclosure provides a composition comprising a first polymer having a high intrinsic viscosity [η] of at least 500 ml / g and a second polymer having a low intrinsic viscosity [η] lower than that of the first polymer and less than 1800 ml / g. More specifically, the present disclosure provides a hydrogel and a drug formed from the composition, and a method for producing a hydrogel.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] Chemically cross-linked polymers - Polymer hydrogels are formed by cross-linking one polymer with another. The polymers are usually modified with reactive groups and cross-linked by chemical reactions.

[0002] There are two main types of crosslinking. One is to crosslink polymers with small molecule crosslinkers. However, small molecules may be toxic to the human body and may cause adverse reactions, so they are not suitable in many situations. Another type of crosslinking is to graft reactive groups on different polymers, and the polymers grafted with different reactive groups can react and form hydrogels. This type of crosslinking can produce hydrogels with desired properties, such as hydrogels with low mechanical strength. Previous studies have shown that hydrogels with low mechanical strength can be prepared by reacting one or more reactive polymers with a large gyration radius (Rg), a large intrinsic viscosity ([η]) or a high molecular weight (MW).

[0003] Therefore, it is necessary to generate hydrogels with the desired properties using appropriately stable polymers required for product manufacturing. Summary of the invention

[0004] The present disclosure provides compositions comprising polymers (e.g., biocompatible polymers) capable of forming hydrogels and methods for preparing and using the same. For example, the composition may include at least one first polymer and at least one second polymer, wherein the first polymer may have an intrinsic viscosity [η] of at least 500 ml / g in the composition, and the second polymer may have an intrinsic viscosity [η] lower than the first polymer and less than 1800 ml / g (e.g., measured by an Ubbelohde viscometer). The concentration of the first polymer in the composition may be up to about 5 mg / ml. The first polymer and the second polymer are stable in the composition and can be stored for a long time (e.g., 24 hours or longer) for appropriate quality control testing and transportation. The composition and the polymers therein can be used to form a manufacturable hydrogel product. The hydrogel formed by the first polymer and / or the second polymer can encapsulate a bioactive agent (e.g., a drug). The bioactive agent can be cumulatively released from the hydrogel.

[0005] In addition, the present disclosure provides a hydrogel formed by the polymer of the present disclosure. In some cases, the hydrogel may be a viscoelastic solid when the G' value is relatively low, and have a higher G' compared to G". In some cases, the hydrogel may be relatively more elastic at lower stress levels, but relatively more viscous at higher stress levels. In some specific cases, a hydrogel with high elasticity at low stress may not necessarily correspond to high elasticity at high stress. In some cases, the hydrogel has a higher viscosity at low shear rates, but a lower viscosity at high shear rates. Therefore, the mechanical properties (such as elastic behavior) of the hydrogel of the present disclosure under different conditions (such as strain, shear rate, frequency) can be adjusted.

[0006] In some embodiments, the first polymer of the present disclosure is not cross-linked itself, and the second polymer is not cross-linked itself. The hydrogel formed according to the present disclosure can have a relatively low G' (e.g., G' is less than about 5 Pa), a higher G' compared to G" (e.g., G" / G'<1), while having a relatively large yield strain (e.g., ≥10%). The hydrogel of the present disclosure can have a low viscosity at high shear rates (e.g., a viscosity of no more than about 0.5 Pa·s), indicating that it may be easily spread on a surface with the help of very little force.

[0007] In one aspect, the present disclosure provides a composition comprising at least one first polymer having a first reactive group and at least one second polymer having a second reactive group, wherein the first polymer has an intrinsic viscosity [η] of at least 500 ml / g, and the second polymer has an intrinsic viscosity [η] lower than that of the first polymer and less than 1800 ml / g, and the concentration of the first polymer in the composition is at most about 5 mg / ml.

[0008] In some embodiments, the first polymer is capable of reacting with the second polymer to form a hydrogel.

[0009] In some embodiments, the first polymer and / or the second polymer are hydrophilic and / or water soluble.

[0010] In some embodiments, the first polymer and / or the second polymer are independently selected from the group consisting of polysaccharides, poly(acrylic acid), poly(hydroxyethyl methacrylate), elastin, collagen, polyethylene glycol, derivatives thereof, and any combination thereof.

[0011] In some embodiments, the first polymer and / or the second polymer are independently selected from the group consisting of hyaluronic acid, guar gum, starch, chitosan, chondroitin sulfate, alginate, carboxymethylcellulose, dextran, derivatives thereof, and any combination thereof.

[0012] In some embodiments, the first polymer and / or the second polymer are independently selected from the group consisting of hyaluronic acid, dextran, derivatives thereof, and any combination thereof.

[0013] In some embodiments, the first polymer comprises a first polymer derivative, the first polymer derivative comprises a first reactive group, and the first polymer derivative is electrophilic.

[0014] In some embodiments, the first reactive group is selected from the group consisting of vinyl, acryl, thiol, olefin, thiol ester, isocyanate, isothiocyanate, alkyl halide, sulfonyl halide, epoxide, imide ester, fluorophenyl ester, carbonate, carbodiimide, disulfide, aziridine, and any combination thereof.

[0015] In some embodiments, the first reactive group is selected from the group consisting of vinyl sulfone, maleimide, acrylate, methacrylate, epoxide, and any combination thereof.

[0016] In some embodiments, the second polymer comprises a second polymer derivative, the second polymer derivative comprises a second reactive group, and the second polymer derivative is nucleophilic.

[0017] In some embodiments, the second reactive group is selected from the group consisting of thiol, amine, azide, hydrazide, diene, hydrazine, hydroxylamine, and any combination thereof.

[0018] In some embodiments, the first polymer has a molecular weight of about 500,000 to about 5,500,000 Daltons.

[0019] In some embodiments, the second polymer has a molecular weight of about 3,000 to about 800,000 Daltons.

[0020] In some embodiments, the molecular weight (MW) ratio between the first polymer and the second polymer in the composition is from about 500:1 to about 1.5:1.

[0021] In some embodiments, the ratio of the radius of gyration (Rg) between the first polymer and the second polymer in the composition is from about 150:1 to about 1:1.

[0022] In some embodiments, the mass ratio between the first polymer and the second polymer in the composition is from about 20:1 to about 1:20.

[0023] In some embodiments, the molar ratio between the first polymer and the second polymer in the composition is from about 4:1 to about 1:500.

[0024] In some embodiments, the first polymer may have an intrinsic viscosity [η] of about 500 ml / g to about 5000 ml / g.

[0025] In some embodiments, the second polymer may have an intrinsic viscosity [η] of about 5 ml / g to about 1800 ml / g.

[0026] In some embodiments, the ratio between the intrinsic viscosities of the first polymer and the second polymer in the composition is from about 500:1 to about 1:1.

[0027] In some embodiments, the derivatives have an average degree of modification (DM) of about 3% to about 50%.

[0028] In some embodiments, the first polymer derivative has a first DM, the second polymer derivative has a second DM, and the ratio between the first DM and the second DM is from about 20:1 to about 1:20.

[0029] In some embodiments, the first polymer derivative is a hyaluronic acid derivative modified with one or more vinyl sulfone groups, a hyaluronic acid derivative modified with one or more maleimide groups, or a combination thereof, and the second polymer derivative is a dextran derivative modified with one or more thiol groups, a hyaluronic acid derivative modified with one or more thiol groups, a polyethylene glycol derivative modified with one or more thiol groups, or a combination thereof.

[0030] In some embodiments, the first polymer and / or the second polymer is contained in the composition in the form of a formed hydrogel.

[0031] In some embodiments, the composition does not include any cross-linking agent different from the first polymer and / or the second polymer.

[0032] In another aspect, the present disclosure provides a hydrogel formed from the composition of the present disclosure.

[0033] In some embodiments, the hydrogels of the present disclosure are biocompatible.

[0034] In some embodiments, the hydrogel has at least one of the following properties: 1) a storage modulus G' not exceeding 5 Pa, as measured in a dynamic oscillatory shear test at 5% strain and 5 rad / s frequency; 2) a viscosity not exceeding about 0.5 mPa·s, as measured in a continuous shear test at a shear rate exceeding about 100 / s, and 3) a loss modulus G" not exceeding about 100% of its storage modulus G', as measured in a dynamic oscillatory shear test at 5% strain and 5 rad / s frequency.

[0035] In another aspect, the present disclosure provides a method for generating a hydrogel, comprising: a) providing a composition of the present disclosure; and b) subjecting the composition to conditions capable of forming a hydrogel.

[0036] In some embodiments, the subjecting comprises incubating the composition at about 15°C to about 50°C.

[0037] In another aspect, the present disclosure provides a pharmaceutical composition comprising the hydrogel of the present disclosure.

[0038] In some embodiments, the hydrogel is formulated to be suitable for drug encapsulation.

[0039] In some embodiments, the pharmaceutical composition comprises a drug, and the drug is encapsulated in the hydrogel.

[0040] Other aspects and advantages of the present disclosure will become apparent to those skilled in the art through the following detailed description, wherein only illustrative embodiments of the present disclosure are shown and described. It will be appreciated that the present disclosure is capable of other and different embodiments, and that its several details are capable of modification in various obvious respects without departing from the present disclosure in all respects. Therefore, the drawings and description are to be regarded as illustrative and not restrictive.

[0041] Incorporated by Reference

[0042] All publications, patents, and patent applications mentioned in this specification are herein incorporated by reference to the same extent as if each individual publication, patent, or patent application was specifically and individually indicated to be incorporated by reference. BRIEF DESCRIPTION OF THE DRAWINGS

[0043] The novel features of the present invention are particularly pointed out in the appended claims. A better understanding of the features and advantages of the present invention will be obtained by referring to the following detailed description and the accompanying drawings (also "figures" and "pictures"), which set forth illustrative embodiments in which the principles of the present invention are employed, wherein:

[0044] Figure 1 The synthesis of HA-VS polymers is described.

[0045] Figure 2 The synthesis of HA-SH polymers is illustrated.

[0046] Figure 3 The formation of a hydrogel of the present disclosure is demonstrated.

[0047] Figure 4A Illustrated are the MW changes measured by agarose hydrogel electrophoresis (AGE) of HA-SH after reaction and after dialysis for 1 day at a solution of approximately 1 mg / ml against pH 4 HCl. Figure 4B The distribution MW measured by AGE of HA and HA-SH is illustrated.

[0048] Figure 5 The GPC curve of HA-VS at 2.6 MDa, 23% DM is illustrated.

[0049] Fig. 6A and6B Examples of the change in MW of HA-SH as a solution at 4°C (6A) and a hydrogel permeation chromatography (GPC) curve of HA-SH as a solution stored at 4°C (6B) are illustrated.

[0050] Fig. 7A and 7B Examples of the change in MW of HA-SH as a solution at 4°C (7A) and the GPC curve of HA-SH as a solution stored at 4°C (7B) are illustrated.

[0051] Fig. 8A , 8B , 8C and 8D illustrate examples of the change in MW (8A) and GPC curve (8B) of dextran-SH at 5% DM, and examples of the change in MW (8C) and GPC curve (8D) of dextran-SH at 12.5% ​​DM.

[0052] Fig. 9 The changing trend of gel G' at different HA-SH concentrations is illustrated.

[0053] Fig.10 The changing trend of gel G' at different HA-VS concentrations is illustrated.

[0054] Fig.11 The changing trend of gel G' under different DM is illustrated.

[0055] Fig.12 The changing trend of G' of the gel formed by dextran-SH is illustrated.

[0056] Fig.13 Illustrated are the MW changes measured by AGE of 16.4% DM and 670 kDa HA-SH after different incubation periods.

[0057] Fig.14A and 14B Illustrated are G' and G" for four hydrogels subjected to frequency sweep testing.

[0058] Fig.15A and 15B Illustrated are G' and G" for four hydrogels subjected to strain sweep testing.

[0059] Fig.16A and 16B The strain responses of four hydrogels subjected to step stress testing are illustrated.

[0060] Fig.17A and 17B The shear viscosities of four hydrogels subjected to continuous shear testing are illustrated.

[0061] Fig.18The release of small molecule moxifloxacin from the hydrogel is demonstrated.

[0062] Fig.19 The release of small molecule levofloxacin from the hydrogel was demonstrated.

[0063] Fig. 20 The release of the protein Bevacizumab from the hydrogel is demonstrated.

[0064] Fig.21 The release of the aptamer from the hydrogel Ap1 is illustrated.

[0065] Fig. 22 The release of the aptamer from the hydrogel Ap2 is illustrated. DETAILED DESCRIPTION

[0066] Although various embodiments of the present invention have been shown and described herein, it will be apparent to those skilled in the art that these embodiments are provided as examples only. Without departing from the present invention, many variations, changes and substitutions may be envisioned by those skilled in the art. It should be understood that various alternatives to the embodiments of the present invention described herein may be employed.

[0067] As used herein, the term "polymer" generally refers to a compound or mixture of compounds that is formed by polymerization and is essentially composed of repeating structural units. In some embodiments, the polymer may be a hydrogel-forming polymer. As used herein, the term "hydrogel-forming polymer" generally refers to a polymer that participates in the formation of a hydrogel. It may be a naturally occurring polymer or a synthetic polymer that is capable of forming a hydrogel. The hydrogel-forming polymer may include a polymer that contributes to the formation of a hydrogel. In some embodiments, the hydrogel-forming polymer does not include a polymer that cannot participate in the formation of a hydrogel, and / or a polymer that cannot form a hydrogel, even if present in the composition of the present disclosure. In some cases, the hydrogel-forming polymer may also be referred to as a "main chain polymer" and a "cross-linked polymer."

[0068] As used herein, the term "hydrogel" generally refers to a gel or gel-like structure comprising one or more polymers suspended in an aqueous solution (e.g., water). All hydrogels have a certain degree of physical attraction between the macromers due to entanglement with each other. Typically, hydrogels used for tissue engineering applications can be enhanced by additional physical interactions or chemical crosslinking.

[0069] As used herein, the term "electrophilic" generally refers to having an affinity for electron pairs. An electrophilic substance (e.g., a molecule or a portion of a molecule) can be an electron pair acceptor. In some embodiments, the electrophilic molecule or group can be selected from the group consisting of vinyl, acryloyl, thiol, olefin, thiol ester, isocyanate, isothiocyanate, haloalkane, sulfonyl halide, epoxide, imine ester, fluorophenyl ester, carbonate, carbodiimide, disulfide, aziridine, and any combination thereof. In some embodiments, the electrophilic molecule or group can include vinyl sulfone, maleimide, acrylate, methacrylate, epoxide, and any combination thereof.

[0070] As used herein, the term "nucleophilic" generally refers to the property of being able to donate electron pairs to form chemical bonds associated with reactions with electrophilic substances. In some embodiments, the term can refer to the nucleophilic nature of a substance and its affinity for electrophiles. In some embodiments, the nucleophilic substance (e.g., a molecule or a portion of a molecule) can be selected from the group consisting of thiols, amines, azides, hydrazides, amines, dienes, hydrazines, hydroxylamines, and any combination thereof.

[0071] As used herein, the term "hydrophilic" generally refers to having an affinity for water, being able to absorb water or being wetted by water. Hydrophilic molecules or portions of molecules interact more thermodynamically favorably with water and other polar substances than with oils or other hydrophobic solvents.

[0072] As used herein, the term "viscosity" generally refers to the resistance property to flow in a fluid or semifluid.

[0073] As used herein, the term "intrinsic viscosity [η]" generally refers to a value measured from a dilute solution of a macromolecule, which contains information about the shape, flexibility, and molar mass of the macromolecule. It is defined as the reduced specific viscosity at the limit of "infinite dilution" or zero concentration. In the present disclosure, the intrinsic viscosity [η] can be measured by an Ubbelohde viscometer or a differential viscometer. Alternatively, the intrinsic viscosity [η] can be calculated from the Mark-Houwink equation according to the established relationship between the intrinsic viscosity and the molecular weight. The [η] of a polymer may be different under different conditions, such as in different solvents, solvents of different compositions (e.g., different salt concentrations), or at different temperatures. Unless otherwise specified, the [η] value in this patent refers to the [η] value under hydrogel formation conditions.

[0074] As used herein, the term "substantially" generally refers to more than a minimal or insignificant amount; whereas "substantially" generally refers to more than a minimal or insignificant amount.

[0075] As used herein, the term "storage modulus G'" generally refers to the elastic response of a material to an oscillating sinusoidal strain, as measured by a dynamic oscillation mode of a rheometer.

[0076] As used herein, the term "loss modulus G" generally refers to the viscous response of a material to an oscillating sinusoidal strain, as measured by a rheometer in dynamic oscillation mode.

[0077] As used herein, the term "average degree of modification (DM)" generally refers to the number of reactive groups per 100 repeating units in a polymer. In the present disclosure, reactive groups can be added to a polymer before or after the polymer is generated. In some embodiments, reactive groups can be added to a polymer during the preparation of the polymer. In some embodiments, reactive groups can be added to a polymer during the modification process. For example, DM can reflect the degree of modification of a polymer derivative.

[0078] As used herein, the term "radius of gyration (Rg)" or "radius of gyration" of a polymer generally refers to the average distance of a polymer chain element from the center of gravity of the chain.

[0079] As used herein, the term "crosslink" generally refers to the bonds that connect one polymer chain to another polymer chain. They can be covalent bonds or ionic bonds. "Polymer chains" can refer to synthetic polymers or natural polymers (e.g., hyaluronic acid).

[0080] As used herein, the term "crosslinking agent" generally refers to an agent that connects one polymer chain to another polymer chain through a bond. The crosslinking agent can achieve crosslinking through covalent bonds or non-covalent bonds. "Polymer chain" can refer to a synthetic polymer, a natural polymer (such as hyaluronic acid), or a derivative of a natural polymer. In polymer chemistry, when a polymer is to be "crosslinked", it generally means that the entire body of the polymer has been exposed to the crosslinking method. The resulting change in mechanical properties depends largely on the crosslink density. Crosslinks can be formed by chemical reactions between polymers.

[0081] As used herein, the term "precursor polymer" generally refers to a polymer used to form another polymer structure or to be further modified. This material can be further polymerized through reactive groups to form a higher molecular weight structure.

[0082] As used herein, the term "composition" generally refers to a product (liquid or solid) of various elements or ingredients.

[0083] As used herein, the term "biocompatible" or "biocompatibility" generally refers to the condition of being compatible with living tissues or systems by not being toxic, injurious, or physiologically reactive and / or not causing immune rejection.

[0084] When used in the context of a numerical value, the term "about" generally refers to a value that is less than 1% to 15% above or below the indicated value (e.g., less than 1%, less than 2%, less than 3%, less than 4%, less than 5%, less than 6%, less than 7%, less than 8%, less than 9%, less than 10%, less than 11%, less than 12%, less than 13%, less than 14%, or less than 15%).

[0085] Where a range of values ​​(e.g., a numerical range) is provided, it is understood that, unless the context clearly dictates otherwise, each intermediate value between the upper and lower limits of the range (to one tenth of the unit of the lower limit) and any other specified or intermediate values ​​within the specified range are encompassed within the present invention. The upper and lower limits of these smaller ranges may be independently included in the smaller ranges and are also encompassed within the present invention, but are subject to any specifically excluded limits within the specified ranges. Where a specified range includes one or two limits, ranges excluding one or both of those included limits are also encompassed within the present invention.

[0086] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those generally understood by those of ordinary skill in the art to which the invention belongs. Although any methods and materials similar or equivalent to the methods and materials described herein can also be used in the practice or testing of the present invention, preferred methods and materials are now described. All publications mentioned herein are incorporated herein by reference to disclose and describe the methods and / or materials associated with citing these publications.

[0087] As used herein, the singular forms "a", "an", and "the" include plural referents unless the context clearly dictates otherwise. Thus, for example, reference to "a particle" includes a plurality of such particles and reference to "a sequence" includes reference to one or more of said sequences and equivalents thereof known to those skilled in the art, and so forth.

[0088] As will be understood by those skilled in the art after reading this disclosure, each individual embodiment described and illustrated herein has discrete components and features that can be easily separated or combined with the features of any of the other several embodiments without departing from the scope or spirit of the present invention. Any enumerated method can be performed in the order of the enumerated events or in any other logically possible order. This is intended to provide support for all such combinations.

[0089] The present disclosure provides compositions comprising one or more hydrogel-forming polymers and methods of making and using the same. The present disclosure also provides a hydrogel and methods of making and using the same.

[0090] In one aspect, the present disclosure provides a composition that may include at least one (e.g., one, two, three, four, five, six, seven, eight, nine, ten or more) first polymer having a high intrinsic viscosity [η] and at least one (e.g., one, two, three, four, five, six, seven, eight, nine, ten or more) second polymer having a low intrinsic viscosity [η]. In some embodiments, the first polymer may have a molecular weight of at least about 500 ml / g (e.g., at least about 500 ml / g, at least about 600 ml / g, at least about 700 ml / g, at least about 800 ml / g, at least about 900 ml / g, at least about 1000 ml / g, at least about 1100 ml / g, at least about 1200 ml / g, at least about 1300 ml / g, at least about 1400 ml / g, at least about 1500 ml / g, at least about 1600 ml / g, at least about 1700 ml / g, at least about 1800 ml / g, at least about 1900 ml / g, at least about 2000 ml / g, at least about 2200 ml / g, at least about 2400 ml / g, at least about 2800 ml / g, at least about 2900 ml / g, at least about 3000 ml / g, at least about 3500 ml / g, at least about 4000 ml / g). The second polymer may have an [η] lower than that of the first polymer and less than about 1800 ml / g (e.g., less than about 1700 ml / g, less than about 1600 ml / g, less than about 1500 ml / g, less than about 1400 ml / g, less than about 1300 ml / g, less than about 1200 ml / g, less than about 1100 ml / g, less than about 1000 ml / g, less than about 900 ml / g, less than about 800 ml / g, less than about 700 ml / g, less than about 600 ml / g, less than about 500 ml / g, less than about 400 ml / g, less than about 300 ml / g, less than about 200 ml / g, less than about 100 ml / g, less than about 20 ml / g, less than about 10 ml / g or less).

[0091] In some embodiments, the first polymer may have an intrinsic viscosity [η] of about 500 ml / g to about 5000 ml / g (e.g., about 500 ml / g to about 4600 ml / g, about 600 ml / g to about 4400 ml / g, about 800 ml / g to about 4200 ml / g, about 1000 ml / g to about 4000 ml / g, about 1500 ml / g to about 3500 ml / g, about 2000 ml / g to about 3500 ml / g, about 2500 ml / g to about 3500 ml / g, etc.). In some embodiments, the first polymer may have an intrinsic viscosity [η] of about 1000 ml / g to about 4000 ml / g, for example, the first polymer may have an intrinsic viscosity [η] of about 2500 ml / g to about 3500 ml / g, as measured by an Ubbelohde viscometer, a hydrogel permeation chromatography coupled with a capillary viscometer, or calculated based on the relationship between published molecular weights and [η].

[0092] In some embodiments, the second polymer may have an intrinsic viscosity [η] of about 5 ml / g to about 1800 ml / g (e.g., about 5 ml / g to about 1600 ml / g, about 5 ml / g to about 1400 ml / g, about 5 ml / g to about 1200 ml / g, about 5 ml / g to about 1000 ml / g, about 5 ml / g to about 500 ml / g, about 5 ml / g to about 400 ml / g, about 5 ml / g to about 300 ml / g, about 5 ml / g to about 250 ml / g, about 10 ml / g to about 200 ml / g, about 10 ml / g to about 150 ml / g, about 15 ml / g to about 100 ml / g, etc.). In some embodiments, [η] may be measured by an Ubbelohde viscometer. For example, the second polymer can have an intrinsic viscosity [η] of about 5 ml / g to about 200 ml / g, as measured by an Ubbelohde viscometer, aqueous gel permeation chromatography coupled with a capillary viscometer, or calculated based on published relationships between molecular weight and [η].

[0093] In some embodiments, the first polymer may have an intrinsic viscosity [η] of about 1000 ml / g to about 4000 ml / g, and the second polymer may have an intrinsic viscosity [η] of about 5 ml / g to about 200 ml / g.

[0094] In the present disclosure, the first polymer has a first intrinsic viscosity [η] ([η]1), and the second polymer has a second intrinsic viscosity [η] ([η]2). In some embodiments, [η]1 may be greater than [η]2, and the ratio between [η]1 and [η]2 may be from about 500:1 to about 1:1 (e.g., from about 500:1 to about 1:1, from about 400:1 to about 1:1, from about 300:1 to about 1:1, from about 200:1 to about 1:1, from about 100:1 to about 1:1, from about 50:1 to about 1:1, from about 3:1 to about 1:1, from about 20:1 to about 1:1, from about 10:1 to about 1:1, [η]1 to about 1:1, about 5:1 to about 1:1, about 500:1 to about 10:1, about 500:1 to about 40:1, about 500:1 to about 50:1, about 500:1 to about 100:1, about 500:1 to about 200:1, about 500:1 to about 300:1, about 500:1 to about 400:1, about 400:1 to about 20:1, about 250:1 to about 30:1, about 150:1 to about 40:1, etc.). For example, the ratio between [η]1 and [η]2 can be about 300:1 to about 25:1.

[0095] In some embodiments, the concentration of the first polymer in the composition may be up to about 5 mg / ml. In some embodiments, the concentration of the first polymer in the composition may be about 0.1 mg / ml to about 4 mg / ml (e.g., about 0.1 mg / ml to about 4 mg / ml, about 0.2 mg / ml to about 3 mg / ml, about 0.3 mg / ml to about 2 mg / ml, about 0.3 mg / ml to about 1.5 mg / ml, etc.). In some embodiments, the concentration of the first polymer in the composition may be about 0.3 mg / ml to about 1.5 mg / ml.

[0096] In some embodiments, the first polymer may be selected from the group consisting of polysaccharides, poly(acrylic acid), poly(hydroxyethyl methacrylate), elastin, collagen, polyethylene glycol, derivatives thereof, and any combination thereof. For example, the first polymer in the composition may include one or more of the following: polysaccharides, one or more types of polysaccharide derivatives, poly(acrylic acid), one or more types of poly(acrylic acid) derivatives, poly(hydroxyethyl methacrylate), one or more types of poly(hydroxyethyl methacrylate) derivatives, elastin, one or more types of elastin derivatives, collagen, one or more types of collagen derivatives, polyethylene glycol, and one or more types of polyethylene glycol derivatives, and any combination thereof.

[0097] In some embodiments, the second polymer may be selected from the group consisting of polysaccharides, poly(acrylic acid), poly(hydroxyethyl methacrylate), elastin, collagen, polyethylene glycol, derivatives thereof, and any combination thereof. For example, the second polymer in the composition may include one or more of the following: polysaccharides, one or more types of polysaccharide derivatives, poly(acrylic acid), one or more types of poly(acrylic acid) derivatives, poly(hydroxyethyl methacrylate), one or more types of poly(hydroxyethyl methacrylate) derivatives, elastin, one or more types of elastin derivatives, collagen, one or more types of collagen derivatives, polyethylene glycol, and one or more types of polyethylene glycol derivatives, and any combination thereof.

[0098] In some embodiments, the first polymer may be selected from the group consisting of polysaccharides, poly(acrylic acid), poly(hydroxyethyl methacrylate), elastin, collagen, polyethylene glycol, derivatives thereof, and any combination thereof, and the second polymer may be selected from the group consisting of polysaccharides, poly(acrylic acid), poly(hydroxyethyl methacrylate), elastin, collagen, polyethylene glycol, derivatives thereof, and any combination thereof.

[0099] In some embodiments, the first polymer may be selected from the group consisting of hyaluronic acid, guar gum, starch, chitosan, chondroitin sulfate, alginate, carboxymethyl cellulose, dextran, derivatives thereof, and any combination thereof. For example, the first polymer in the composition may include one or more of the following: hyaluronic acid, one or more types of hyaluronic acid derivatives, guar gum, one or more types of guar gum derivatives, starch, one or more types of starch derivatives, chitosan, one or more types of chitosan derivatives, chondroitin sulfate, one or more types of chondroitin sulfate derivatives, alginate, one or more types of alginate derivatives, carboxymethyl cellulose and one or more types of carboxymethyl cellulose derivatives, dextran, one or more types of dextran derivatives, and any combination thereof.

[0100] In some embodiments, the second polymer may be selected from the group consisting of hyaluronic acid, guar gum, starch, chitosan, chondroitin sulfate, alginate, carboxymethyl cellulose, dextran, derivatives thereof, and any combination thereof. For example, the second polymer in the composition may include one or more of the following: hyaluronic acid, one or more types of hyaluronic acid derivatives, guar gum, one or more types of guar gum derivatives, starch, one or more types of starch derivatives, chitosan, one or more types of chitosan derivatives, chondroitin sulfate, one or more types of chondroitin sulfate derivatives, alginate, one or more types of alginate derivatives, carboxymethyl cellulose and one or more types of carboxymethyl cellulose derivatives, dextran, one or more types of dextran derivatives, polyethylene glycol, one or more types of polyethylene glycol derivatives, and any combination thereof.

[0101] In some embodiments, the first polymer may be selected from the group consisting of hyaluronic acid, guar gum, starch, chitosan, chondroitin sulfate, alginate, carboxymethyl cellulose, dextran, derivatives thereof, and any combination thereof, and the second polymer may be selected from the group consisting of hyaluronic acid, guar gum, starch, chitosan, chondroitin sulfate, alginate, carboxymethyl cellulose, dextran, polyethylene glycol, derivatives thereof, and any combination thereof.

[0102] In some embodiments, the first polymer may be selected from the group consisting of hyaluronic acid, dextran, derivatives thereof, and any combination thereof. For example, the first polymer in the composition may include one or more of: hyaluronic acid, one or more types of hyaluronic acid derivatives, dextran, one or more types of dextran derivatives, and any combination thereof.

[0103] In some embodiments, the second polymer may be selected from the group consisting of hyaluronic acid, dextran, derivatives thereof, and any combination thereof. For example, the second polymer in the composition may include one or more of: hyaluronic acid, one or more types of hyaluronic acid derivatives, dextran, one or more types of dextran derivatives, polyethylene glycol, and any combination thereof.

[0104] In some embodiments, the first polymer may be selected from the group consisting of hyaluronic acid, dextran, derivatives thereof, and any combination thereof, and the second polymer may be selected from the group consisting of hyaluronic acid, dextran, derivatives thereof, and any combination thereof.

[0105] For example, the first polymer in the composition may include one or more of the following: a hyaluronic acid derivative, and the second polymer may be a hyaluronic acid derivative. For another example, the first polymer may be a hyaluronic acid derivative and the second polymer may be a dextran derivative.

[0106] In some embodiments, the composition of the present disclosure may include at least a first polymer derivative and a second polymer derivative, wherein the first polymer derivative may include a first reactive group and the second polymer derivative may include a second reactive group. The first reactive group may be different from the second reactive group.

[0107] According to any aspect of the present disclosure, a polymer (e.g., a hydrogel-forming polymer) can be modified with one or more reactive groups, for example, to become a polymer derivative of the present disclosure. In one example, a polymer (e.g., a hydrogel-forming polymer) of the present disclosure can be modified with one or more vinyl sulfone groups (or with a molecule comprising one or more vinyl sulfone groups). In another example, a polymer (e.g., a hydrogel-forming polymer) of the present disclosure can be modified with one or more thiol groups (or with a molecule comprising one or more thiol groups).

[0108] In the present disclosure, the first polymer may include a first polymer derivative, which may include a first reactive group, and the first polymer derivative may be electrophilic. In some embodiments, the first reactive group may be selected from the group consisting of vinyl, maleimide, acrylate, methacrylate, epoxide, mercaptan, olefin, thiol ester, isocyanate, isothiocyanate, alkyl halides, sulfonyl halides, epoxides, imine esters, fluorophenyl esters, carbonates, carbodiimides, disulfides, aziridines, and any combination thereof. In some embodiments, the first reactive group may be selected from the group consisting of vinyl, acryloyl, mercaptan, olefin, thiol ester, isocyanate, isothiocyanate, alkyl halides, sulfonyl halides, epoxides, imine esters, fluorophenyl esters, carbonates, carbodiimides, disulfides, aziridines, and any combination thereof.

[0109] In some embodiments, the first reactive group can be selected from vinyl sulfone, maleimide, acrylate, methacrylate, epoxide, and any combination thereof.

[0110] In the present disclosure, the second polymer may include a second hydrogel-forming polymer derivative, the second polymer derivative may include a second reactive group, and the second hydrogel-forming polymer derivative may be nucleophilic.

[0111] In some embodiments, the second reactive group can be selected from the group consisting of thiols, amines, azides, hydrazides, dienes, hydrazines, hydroxylamines, and any combination thereof.

[0112] In some embodiments, the first reactive group can be selected from the group consisting of vinyl, maleimide, acrylate, methacrylate, epoxide, thiol, olefin, thiol ester, isocyanate, isothiocyanate, alkyl halide, sulfonyl halide, epoxide, imide ester, fluorophenyl ester, carbonate, carbodiimide, disulfide, aziridine, and any combination thereof, and the second reactive group can be selected from the group consisting of thiol, amine, azide, hydrazide, diene, hydrazine, hydroxylamine, and any combination thereof.

[0113] In some embodiments, the first reactive group may be selected from vinyl sulfone, maleimide, acrylate, methacrylate, epoxide, and any combination thereof, and the second reactive group may be selected from thiol, amine, azide, hydrazide, diene, hydrazine, hydroxylamine, and any combination thereof.

[0114] For example, the first reactive group can include a vinyl sulfone and the second reactive group can include a thiol.

[0115] In some embodiments, in the composition, the first reactive group can include one or more vinyl sulfones and the second reactive group can include one or more thiols.

[0116] In some embodiments, the first polymer derivative is capable of reacting with the second polymer derivative to form a hydrogel.

[0117] In some embodiments, the first polymer can have a molecular weight of about 500,000 to about 5,500,000 Daltons (e.g., about 500,000 to about 5,500,000 Daltons, about 1,000,000 to about 5,500,000 Daltons, about 1,500,000 to about 5,500,000 Daltons, about 2,000,000 to about 5,500,000 Daltons, about 2,5 000,000 to about 5,500,000 daltons, about 3,000,000 to about 5,500,000 daltons, about 3,500,000 to about 5,500,000 daltons, about 4,000,000 to about 5,500,000 daltons, about 4,500,000 to about 5,500,000 daltons, or about 500,000 to about 5,000,000 daltons, about 500,000 to about 5,000,000 daltons, about 0,000 to about 4,500,000 Daltons, about 500,000 to about 4,000,000 Daltons, about 500,000 to about 3,500,000 Daltons, about 1,000,000 to about 3,000,000 Daltons, about 1,000,000 to about 2,500,000 Daltons, about 1,000,000 to about 2,000,000 Daltons, about 1,000,000 to about 3,000,000 Daltons, about 1,000,000 to about 4,500,000 Daltons, about 500,000 to about 4,000,000 Daltons, about 500,000 to about 3,500,000 Daltons In some embodiments, the first polymer may have a molecular weight of about 1,000 to about 1,500,000 Daltons, or about 1,500,000 to about 5,000,000 Daltons, about 2,000,000 to about 4,500,000 Daltons, about 2,000,000 to about 4,000,000 Daltons, about 2,000,000 to about 3,500,000 Daltons, about 2,000,000 to about 3,000,000 Daltons, etc. In some embodiments, the first polymer may be hyaluronic acid.

[0118] In some embodiments, the second polymer can have a molecular weight of about 3,000 to about 800,000 Daltons (e.g., about 3,000 to about 800,000 Daltons, about 5,000 to about 700,000 Daltons, about 10,000 to about 600,000 Daltons, about 15,000 to about 500,000 Daltons, about 20,000 to about 400,000 Daltons, about 20,000 to about 3 00,000 Daltons, about 20,000 to about 200,000 Daltons, about 20,000 to about 100,000 Daltons, about 20,000 to about 90,000 Daltons, about 20,000 to about 80,000 Daltons, about 20,000 to about 70,000 Daltons, about 20,000 to about 60,000 Daltons, about 20,000 to about 50,000 Daltons, etc.). In some embodiments, the second polymer can have a molecular weight of about 20,000 to about 800,000 Daltons (e.g., about 20,000 to about 800,000 Daltons, about 20,000 to about 700,000 Daltons, about 20,000 to about 600,000 Daltons, about 20,000 to about 500,000 Daltons, about 20,000 to about 400,000 Daltons, about 20,000 to about 300,000 Daltons, about 20,000 to about 200,000 Daltons, about 20,000 to about 100,000 Daltons, about 20,000 to about 90,000 Daltons, about 20,000 to about 80,000 Daltons, about 20,000 to about 70,000 Daltons, about 20,000 to about 60,000 Daltons, about 20,000 to about 50,000 Daltons, etc.).

[0119] In some embodiments, the molecular weight (MW) ratio between the first polymer and the second polymer in the composition can be from about 500:1 to about 1.5:1 (e.g., from about 500:1 to about 1.5:1, from about 450:1 to about 1.5:1, from about 400:1 to about 1.5:1, from about 350:1 to about 1.5:1, from about 300:1 to about 1.5:1, from about 250:1 to about 1.5:1, from about 200:1 to about 1.5:1, from about 150:1 to about 1.5:1, from about 100:1 to about 1.5:1, etc.).

[0120] In the present disclosure, the first polymer in the composition can have a radius of gyration (Rg) greater than about 30 nm (e.g., about 30 nm to about 500 nm, about 50 nm to about 450 nm, about 100 nm to about 400 nm, about 150 nm to about 350 nm, about 150 nm to about 300 nm, about 150 nm to about 250 nm, etc.). In some embodiments, the first polymer in the composition can have an Rg of about 30 nm to about 500 nm. In some embodiments, the first polymer in the composition can have an Rg of about 150 nm to about 250 nm.

[0121] The second polymer in the composition can have a radius of gyration (Rg) of less than 100 nm (e.g., about 1 nm to about 100 nm, about 3 nm to about 90 nm, about 3 nm to about 80 nm, about 3 nm to about 70 nm, about 3 nm to about 60 nm, about 3 nm to about 50 nm, about 3 nm to about 40 nm, about 3 nm to about 30 nm, about 3 nm to about 20 nm, about 5 nm to about 20 nm, etc.). In some embodiments, the second polymer in the composition can have an Rg of about 3 nm to about 100 nm. In some embodiments, the second polymer in the composition can have an Rg of about 5 nm to about 20 nm.

[0122] In some embodiments, the ratio of the radius of gyration (Rg) between the first polymer and the second polymer in the composition can be about 150:1 to about 1:1 (e.g., about 150:1 to about 1:1, about 100:1 to about 1:1, about 80:1 to about 1:1, about 60:1 to about 1:1, about 50:1 to about 1:1, about 30:1 to about 1:1, about 30:1 to about 5:1, about 30:1 to about 10:1, etc.). In some embodiments, the ratio of the radius of gyration (Rg) between the first polymer and the second polymer in the composition can be greater than 1:1 (e.g., about 150:1 to about 1.1:1, about 100:1 to about 1.1:1, about 80:1 to about 1.1:1, about 60:1 to about 1.1:1, about 50:1 to about 1.1:1, about 30:1 to about 1.1:1, about 30:1 to about 5:1, about 30:1 to about 10:1, etc.). For example, the ratio of the radius of gyration (Rg) between the first polymer and the second polymer in the composition may be about 30:1 to about 10:1.

[0123] In some embodiments, the molar ratio between the first polymer and the second polymer in the composition can be from about 4:1 to about 1:500 (e.g., from about 4:1 to about 1:500, from about 3:1 to about 1:500, from about 2:1 to about 1:500, from about 1:1 to about 1:500, from about 4:1 to about 1:400, from about 4:1 to about 4:300, from about 4:1 to about 4:200, from about 4:1 to about 1:100, from about 3:1 to about 1:400, from about 2:1 to about 1:300, from about 1:1 to about 1:200, from about 1:1 to about 1:100, from about 1:1 to about 1:500, etc.). For example, the molar ratio between the first polymer and the second polymer in the composition can be from about 1:1 to about 1:50.

[0124] In some embodiments, the derivatives may have an average degree of modification (DM) of about 3% to about 50% (e.g., about 4% to about 45%, about 5% to about 40%, about 6% to about 40%, about 7% to about 40%, about 8% to about 39%, about 8% to about 38%, about 8% to about 35%, about 9% to about 32%, about 8% to about 30%, about 10% to about 30%, about 12% to about 30%, about 13% to about 30%, about 14% to about 30%, about 15% to about 35%, or about 15% to about 30%).

[0125] In some cases, the first polymer derivative can be modified with one or more vinyl sulfone groups and the second polymer derivative can be modified with one or more thiol groups.The first polymer derivative can react with the second polymer derivative to form a hydrogel.

[0126] In the present disclosure, the first polymer derivative can be a dextran derivative modified with one or more vinyl sulfone groups, a hyaluronic acid derivative modified with one or more vinyl sulfone groups, a dextran derivative modified with one or more maleimide groups, a hyaluronic acid derivative modified with one or more maleimide groups, a dextran derivative modified with one or more acrylate groups, a hyaluronic acid derivative modified with one or more acrylate groups, a dextran derivative modified with one or more methacrylate groups, a hyaluronic acid derivative modified with one or more methacrylate groups, or a combination thereof. For example, the first polymer derivative can be a dextran derivative modified with one or more vinyl sulfone groups, a hyaluronic acid derivative modified with one or more vinyl sulfone groups, or a hyaluronic acid derivative modified with one or more maleimide groups.

[0127] In the present disclosure, the second polymer derivative can be a dextran derivative modified with one or more thiol groups, a hyaluronic acid derivative modified with one or more thiol groups, a dextran derivative modified with one or more amine groups, a hyaluronic acid derivative modified with one or more amine groups, or a combination thereof. For example, the second polymer derivative can be a dextran derivative modified with one or more thiol groups, a hyaluronic acid derivative modified with one or more thiol groups.

[0128] In the present disclosure, the first polymer derivative can be a dextran derivative modified with one or more vinyl sulfone groups, a hyaluronic acid derivative modified with one or more vinyl sulfone groups, a dextran derivative modified with one or more maleimide groups, a hyaluronic acid derivative modified with one or more maleimide groups, a dextran derivative modified with one or more acrylate groups, a hyaluronic acid derivative modified with one or more acrylate groups, a dextran derivative modified with one or more methacrylate groups, a hyaluronic acid derivative modified with one or more methacrylate groups, or a combination thereof, and the second polymer derivative can be a dextran derivative modified with one or more thiol groups, a hyaluronic acid derivative modified with one or more thiol groups, a dextran derivative modified with one or more amine groups, a hyaluronic acid derivative modified with one or more amine groups, or a combination thereof. In some cases, the first polymer derivative can be a dextran derivative modified with one or more vinyl sulfone groups, a hyaluronic acid derivative modified with one or more vinyl sulfone groups, and the second polymer derivative can be a dextran derivative modified with one or more thiol groups, a hyaluronic acid derivative modified with one or more thiol groups. The first polymer derivative can react with the second polymer derivative to form a hydrogel.

[0129] For example, the first polymer derivative may include a hyaluronic acid derivative (HA-VS) modified with one or more vinyl sulfone groups, and the second polymer derivative may include a hyaluronic acid derivative (HA-SH) modified with one or more thiol groups. For another example, the first polymer derivative may be a hyaluronic acid derivative (HA-VS) modified with one or more vinyl sulfone groups, and the second polymer derivative may be a dextran derivative (dextran-SH) modified with one or more thiol groups. For another example, the first polymer derivative may be a hyaluronic acid derivative (HA-MI) modified with one or more maleimide groups, and the second polymer derivative may be a hyaluronic acid derivative (HA-SH) modified with one or more thiol groups. Under appropriate conditions, the first polymer derivative can react with the second polymer derivative to form a polymer-polymer hydrogel.

[0130] In some embodiments, the first polymer may be included in the composition in the form of a formed hydrogel.In some embodiments, the second polymer may be included in the composition in the form of a formed hydrogel.

[0131] In some embodiments, the composition may not include any cross-linking agent other than the one or more polymers.

[0132] In some embodiments, the composition may include a buffer. The buffer may be an aqueous solution, and may include water and a suitable salt for adjusting the pH or buffering capacity of the aqueous solution.

[0133] The polymers in the compositions of the present disclosure may have excellent stability for long-term storage. The polymers of the present disclosure will not degrade during long-term storage. The polymers of the present disclosure cannot crosslink or form aggregates with themselves for long-term storage. The polymers of the present disclosure may have a stable molecular weight range.

[0134] In another aspect, the present disclosure provides a hydrogel formed from the composition of the present disclosure. In some embodiments, the hydrogel of the present disclosure can be biocompatible.

[0135] In some cases, substantially all of the polymers in the composition are capable of forming a hydrogel, and in some cases, the composition may not include any cross-linking agent other than the one or more polymers.

[0136] Hydrogels according to the present disclosure may have one or more specific characteristics / properties.

[0137] The hydrogels of the present disclosure can have a storage modulus G' of no more than 5 Pa (e.g., no more than 4 Pa, no more than 3.5 Pa, no more than 3 Pa, no more than 2.5 Pa, at least 2.4 Pa, at least 2.2 Pa, at least 2 Pa, at least 1.8 Pa, no more than 1.6 Pa, no more than 1.5 Pa, no more than 1.4 Pa, no more than 1.2 Pa, no more than 1.0 Pa, no more than 0.8 Pa, no more than 0.7 Pa, no more than 0.6 Pa, no more than 0.5 Pa, no more than 0.4 Pa, no more than 0.3 Pa, no more than 0.2 Pa, no more than 0.1 Pa, or less) as measured in a dynamic oscillatory shear test at 5% strain and 5 rad / s frequency.

[0138] The hydrogels of the present disclosure may have a viscosity of no more than about 100 mPa·s, as measured in a continuous shear test at a frequency shear rate exceeding about 1000 / s. The hydrogels of the present disclosure may have a viscosity of at least about 500 mPa·s, as measured in a continuous shear test at a frequency shear rate exceeding about 0.1 / s. The shear viscosity at 0.1 / s is at least 10 times higher than the shear viscosity at 1000 / s.

[0139] The hydrogels of the present disclosure can have a loss modulus G' of no more than about 100% (e.g., no more than about 90%, no more than about 80%, no more than about 70%, no more than about 60%, no more than about 55%, no more than about 50%, no more than about 45%, no more than about 40%, no more than about 35%, no more than about 30%, no more than about 25%, or no more than about 20%) of its storage modulus G' as measured in a dynamic oscillatory shear test at 5% strain and 5 rad / s frequency.

[0140] In some embodiments, the composition can have a pH of about 6.0 to about 8.0 (e.g., about 6.1 to about 7.9, about 6.2 to about 7.7, about 6.3 to about 7.7, about 6.4 to about 7.4, about 6.5 to about 7.3, about 6.6 to about 7.2, about 6.7 to about 7.1, about 6.8 to about 7, about 6.3 to about 6.8, about 6.3 to about 6.7, or about 6.4 to about 6.6).

[0141] The rheometer can be used to measure storage modulus, loss modulus, and can be used in dynamic oscillatory shear testing. In another example, the rheometer can include a displacement sensor (e.g., a linear variable differential transformer) that can measure the voltage change caused by the movement of the instrument probe through the magnetic core. The rheometer can also include a temperature control system or heating furnace, a drive motor (e.g., a linear motor for probe loading that can provide the load for the applied force), a drive shaft support and a guide system for guiding the force from the motor to the sample, and one or more sample fixtures for holding the sample being tested.

[0142] Different types of rheometer analyzers can be used. For example, a forced resonance analyzer or a free resonance analyzer can be used. A free resonance analyzer can measure the damped free oscillation of the sample by suspending and swinging the sample being tested. A forced resonance analyzer can force the sample to oscillate at a specific frequency and may be reliable for performing temperature scans. The analyzer can be used for both stress (force) and strain (displacement) control. For example, in strain control, the probe can be displaced, and the stress generated by the sample can be measured by implementing a force balance sensor, which can use different axes. In stress control, a set force can be applied, and the strain or displacement generated by the sample can be measured, and several other experimental conditions (temperature, frequency or time) can be changed. Stress and strain can be applied by a torsion or axial analyzer. Using a torsion analyzer, force is applied in the form of a torsional motion. An axial analyzer can be used for bending, tension and / or compression testing.

[0143] A variety of testing modes can be used to probe the viscoelastic properties of polymers and hydrogels, such as temperature sweep testing, frequency sweep testing, strain sweep testing, step stress testing, dynamic stress-strain testing, continuous shear testing, or a combination thereof.

[0144] Rheometers can measure a variety of mechanical properties. These properties include storage modulus (G'), loss modulus (G"), complex modulus (G*), loss angle (tan(δ)), complex viscosity (η*), its in-phase (η') and out-of-phase components (η"), complex compliance (J*), storage compliance (J'), loss compliance (J"), viscosity (η), etc.

[0145] For example, in a dynamic oscillatory shear test, a sinusoidal force (e.g., stress) can be applied to a material and the resulting displacement (strain) can be measured. For a perfectly elastic solid, the strain and stress generated may be completely in phase. For a purely viscous fluid, there may be a 90-degree phase lag between the strain and the stress. Viscoelastic polymers or hydrogels with properties in between may have a phase lag during the test, and the storage modulus and loss modulus can be calculated accordingly.

[0146] In another aspect, the present disclosure provides a method for generating a hydrogel (e.g., a hydrogel of the present disclosure). The method may include a) providing a composition (e.g., a composition comprising one or more polymers of the present disclosure); and b) subjecting the composition to conditions capable of forming a hydrogel (e.g., capable of crosslinking the polymers to form a hydrogel). For example, the conditions may include incubating the composition at about 15°C to about 50°C.

[0147] In some cases, the method can include cross-linking polymers in solution to generate a hydrogel. For example, conditions that can form a hydrogel can also cross-link polymers in solution.

[0148] For example, the method may include: 1) preparing a first polymer (or a first polymer derivative) and a second polymer (or a second polymer derivative) (e.g., the first polymer may include hyaluronic acid modified with one or more vinyl sulfone groups; and the second polymer may include hyaluronic acid, dextran, or polyethylene glycol modified with one or more thiol groups) in water, adjusting the pH (e.g., by adding a buffer solution); 2) mixing the polymer of the first polymer with the polymer of the second polymer in a pre-set ratio, the concentration of the polymers in the composition being as defined in the present disclosure; and 3) incubating the mixture under conditions that allow the formation of a hydrogel according to the present disclosure.

[0149] In some embodiments, the composition may not include any cross-linking agent that is different from the polymer in the composition (eg, the first polymer derivative, or the second polymer derivative).

[0150] In some embodiments, the composition may not include any small molecule cross-linking agents.

[0151] In one specific example, the first polymer derivative is hyaluronic acid modified with one or more vinyl sulfone groups (e.g., HA-VS), and the second polymer derivative is hyaluronic acid or dextran modified with one or more thiol groups (e.g., HA-SH or dextran-SH).

[0152] In another aspect, the present disclosure provides a pharmaceutical composition comprising the hydrogel. The pharmaceutical composition may further comprise a pharmaceutically acceptable adjuvant, a drug and / or a diagnostic compound. Suitable pharmaceutically acceptable adjuvants, drugs and / or diagnostic compounds may be water-soluble, slightly soluble in water and water-insoluble pharmaceutical compounds. The pharmaceutical composition may be in any form. The appropriate form will depend in part on the intended mode of application and location of application.

[0153] In the present disclosure, the composition, hydrogel and / or pharmaceutical composition may further comprise a bioactive agent (e.g., an active pharmaceutical ingredient or a drug), and the bioactive agent is encapsulated in the composition, hydrogel and / or pharmaceutical composition. The bioactive agent can be a small molecule, a protein, a peptide, an oligonucleotide, an aptamer or a nucleic acid. For example, the bioactive agent can be an antibacterial agent, an antifungal agent, an antiviral agent, an anti-inflammatory agent, an immunosuppressant, an antibiotic, an antibody, an angiogenesis inhibitor. For example, the bioactive agent can be suitable for eye diseases or conditions. The bioactive agent can be cumulatively released from the hydrogel over a period of more than 3 days, 3 days, 2 days, 1 day, 12 hours, 8 hours, 4 hours, 3 hours, 2 hours, 1 hour or less.

[0154] Example

[0155] The following examples are presented in order to provide those of ordinary skill in the art with a complete disclosure and description of how to make and use the invention, and are not intended to limit the scope of what the inventors regard as their invention, nor are they intended to represent that the following experiments are all or the only experiments performed. Efforts have been made to ensure the accuracy of the numbers used (e.g., amounts, temperatures, etc.), but some experimental errors and deviations should be taken into account. Unless otherwise indicated, parts are parts by weight, molecular weight is weight average molecular weight, temperature is degrees Celsius, and pressure is at or near atmospheric pressure. Standard abbreviations may be used, such as bp, base pairs; kb, kilobase; pl, picoliter; s or sec, seconds; min, minutes; h or hr, hours; aa, amino acids; nt, nucleotides; im, intramuscular; ip, intraperitoneal; sc, subcutaneous; and the like.

[0156] Example 1 Measurement of Rg and [η]

[0157] The Rg and [η] of a polymer can be measured directly, for example by aqueous gel permeation chromatography coupled with a multi-angle laser light scattering (MALL) detector and a capillary viscometer. Rg and [η] have been measured for many polymers, such as hyaluronic acid (HA) (Mendichi R et al., Evaluation of radius of gyration and intrinsic viscosity molar mass dependence and stiffness of hyaluronan. Biomacromolecules. 2003; 4(6): 1805-1810.), dextran (Ioan, CE et al., Structure properties of dextran. 2. dilute solution. Macromolecules, 2000; 33(15), 5730-5739. or Kasaai M.R., Dilute solution properties and degree of chain branching for dextran, Carbohydrate Polymers 88 (2012) 373–381.), carboxymethyl cellulose (Hoogendam, CW et al., Persistence length of carboxymethyl cellulose as evaluated from sizeexclusion chromatography and potentiometric titrations. Macromolecules, 1998: 31(18), 6297–6309, or Sitaramaiah and Gorning, Hydrodynamic Studies on Sodium Carboxymethyl Cellulose iFFIGn Aqueous Solutions, Journal of Polymer Science, 1962; (58) 1107-1131., or E. Arinaitwe, M.Pawlik, "Dilute solution properties of carboxymethyl celluloses of various molecular weights and degrees of substitution," Carbohydrate Polymers 99 (2014) 423–431.) and polyethylene glycol (Devanand K, Selser JC. "Asymptotic behavior and long-range interactions in aqueous solutions of poly(ethylene oxide). Macromolecules. 1991; 24(22): 5943-5947., or Wu, X. et al., "Viscoelasticity of poly(ethylene glycol) in aqueous solutions of potassium sulfate: a comparison of quartz crystal microbalance with conventional methods.)》PolymerJournal.,2019:doi:10.1038 / s41428-018-0162-3). .

[0158] Some Rg and [η] values ​​are given in Tables 1, 2 and 3.

[0159] Table 1 Rg and [η] values ​​of 500 KDa MW polymers

[0160] polymer HA Dextran Carboxymethyl cellulose Polyethylene glycol Rg(nm) ~75 ~20 ~70 ~45 [η](ml / g) ~1000 50 ~1800 300

[0161] Table 2: Rg and [η] values ​​of HA with different MW

[0162] MW(kDa) 10 29 65 120 670 2600 Rg(nm) 6.7 12.6 20.3 29.3 81.6 183 [η](ml / g) 21.6 66.5 106 303 1156 2960

[0163] Table 3 Rg and [η] values ​​of dextran with different MW

[0164] MW(kDa) 40 70 150 Rg(nm) 6.2 8 ~10 [η](ml / g) 18.9 25.2 37

[0165] Example 2 Preparation of polymer derivatives

[0166] 2.1 Preparation of HA-VS

[0167] As Yu and Chau (Biomacromolecules 2015, 16(1), 56-65) Figure 1 ), hyaluronic acid (HA) was modified with suspended VS. Briefly, HA was dissolved in deionized water (DI water). The concentration ranged from 0.1 mg / ml to 40 mg / ml, depending on the molecular weight (MW) of HA. For high MW HA (e.g., MW>1 MDa), the concentration was lower; for low MW HA (e.g., MW<100 kDa), the concentration was higher.

[0168] After complete dissolution, 5 M NaOH was added dropwise to the polymer solution to a final concentration of 0.1 M. Divinyl sulfone (DVS) was added immediately under vigorous mixing. The molar ratio between DVS and HA hydroxyl groups (OH) was at least 1.25:1. The DVS concentration and reaction time were selected according to the target degree of modification (DM). For a given reaction time, the degree of modification also depends on the concentrations of HA and DVS, the temperature and the final NaOH concentration. The reaction was terminated by adding 1 M HCl to lower the pH to 3.5-4.5. The polymer was purified by membrane separation using a dialysis bag or tangential flow filtration against deionized water. Unless otherwise stated, the purified polymer was stored as a solution at 4 °C. To measure the degree of modification (DM), HA-VS was freeze-dried and filtered through 1 H NMR determination.

[0169] 2.2 Preparation of HA-SH

[0170] As Yu and Chau (Biomacromolecules 2015, 16(1), 56-65) Figure 2), hyaluronic acid (HA) was modified with a hanging thiol (SH) group. Briefly, HA was first modified to HA-VS (as described in Example 2.1). The HA-VS solution was purged with N2 for at least 20 minutes. Dithiothreitol (DTT) (depending on which DTT concentration is higher) was dissolved in water (pH about 5.5) at about 400 mg / ml in a 10-fold molar excess relative to the vinyl sulfone (VS) group or the amount required to prepare a 0.05M DTT solution and then added to the HA-VS solution after purging with N2 for at least 5 minutes. The pH value of the HA-VS / DTT solution was about 4, and the system continued to be purged with N2. Afterwards, 0.5M phosphate buffer (PB) of HA-VS with a volume of 1 / 10 was purged with N2 for at least 5 minutes and added to the HA-VS / DTT solution. The reaction was carried out for at least 25 minutes. The reaction was terminated by adding 1M HCl to reduce the pH to 3.5-4.5. The polymers were purified by membrane separation using dialysis bags or tangential flow filtration against deionized water adjusted to pH 4 by HCl. Unless otherwise stated, the purified polymers were stored in solution at 4° C. The degree of modification (DM) was determined by the Ellman assay of HA-SH.

[0171] 2.3 Preparation of dextran-SH

[0172] Vinyl sulfone (VS) and thiol (SH) functionalized dextran, dextran-VS, and dextran-SH were synthesized using a previously reported method (see Y. Yu and Y. Chau, "One-step 'click' method for generating vinyl sulfone groups on hydroxyl-containing water-soluble polymers," Biomacromolecules, Vol. 13, pp. 937–942, 2012.). Briefly, divinyl sulfone (DVS) reacted with the hydroxyl groups on dextran under aqueous, alkaline conditions to generate dextran-VS ( Figure 1 ). Dithiothreitol (DTT) was used to react with the VS group on dextran-VS in phosphate buffer solution to prepare dextran-SH ( Figure 2 ) to obtain thiol-functionalized dextran, the functionalization protocol was similar to that of Example 2.2. The polymer was purified by membrane separation using a dialysis bag or tangential flow filtration against deionized water adjusted to pH 4 by HCl. Unless otherwise specified, the purified polymer was stored in solution at 4°C. 1 The DM of dextran-VS was determined by H NMR, and the DM of dextran-SH was determined by the Ellman assay.

[0173] Example 3 Stability of modified polymers with high intrinsic viscosity [η]

[0174] HA-SH and HA-VS were modified according to Examples 2.2 and 2.1. To demonstrate the stability of high molecular weight HA, these HA derivatives were modified from HA with a molecular weight of 2.6 MDa ([η] = 2960 ml / g, Rg = 183 nm). The stability of HA-SH was evaluated by agarose hydrogel electrophoresis (AGE), and the stability of HA-VS was evaluated by gel permeation chromatography (GPC).

[0175] The AGE protocol has been modified from previous reports (Lee and Cowman, "An agarose gel electrophoretic method for analysis of hyaluronan molecular weight distribution, "Analytical Chemistry, 1994: 219; 278-287). Briefly, HA-SH samples at approximately 15% DM in AGE loading buffer were loaded into an agarose gel consisting of 5 mg / ml high melting point agarose (Solarbio, Beijing, China) in TEA buffer. After electrophoresis at 80 mV for 1 hour, the hydrogel was stained overnight with 0.005% Stain-All (Sigma) in 50% ethanol. The hydrogel was retained with 10% ethanol.

[0176] The GPC conditions are listed below:

[0177] HPLC: Waters 2695

[0178] Differential reflectance index detector: Waters 2414

[0179] Mobile phase: 0.2M NaCl and 0.01% sodium azide solution

[0180] Flow rate: 0.5mL / min

[0181] Column: Ultrahydrogel Linear, 7.8×300 mm, WAT011545, 005C181201, No. KNC-COL-003.

[0182] The column oven temperature was 35°C and the detector temperature was 30°C.

[0183] Figure 4A-4BThe results showed that HA-SH derived from 2.6 MDa HA (intrinsic viscosity exceeding 1800 ml / g) was not stable as a solution. Figure 4A Lanes 2 and 4 of Figure 4 show the AGE results for unmodified HA, and Figure 4A Lanes 1 and 3 of HA-SH show the AGE results of HA-SH after reaction and after dialysis for 1 day against pH 4 deionized water (pH adjusted with HCl) at a solution of about 1 mg / ml. The results show that the molecular weight of HA-SH is normal after reaction, but after dialysis for 1 day under acidic conditions, the molecular weight of HA-SH increases, as can be seen from the diffusion near the pores in lane 3. Figure 4B Lanes 2 and 3 of Figure 3 show another AGE result of HA-SH and unmodified HA, respectively.

[0184] Furthermore, if HA-SH is lyophilized, the lyophilized powder cannot be dissolved in solution again and will form a gel.

[0185] In contrast, HA-VS is stable as a solution for a long time ( Figure 5 ).

[0186] Example 4 Stability of Modified Polymers with Low Intrinsic Viscosity [η]

[0187] HA-SH and dextran-SH (i.e., Dex-SH) modified from HA of about 65 kDa ([η] = 106 ml / g), 670 kDa ([η] = 1156 ml / g), and dextran of about 45 kDa ([η] = 20 ml / g) were used as examples to show the stability of low intrinsic viscosity polymers. HA-SH was prepared as described in Example 2.2. Dex-SH was prepared as described in Example 2.3. The molecular weight stability of the samples was evaluated by GPC, and the test method was as described in Example 3.

[0188] The molecular weight (MW) and polydispersity (PDI) of the polymers were estimated by comparison to a universal calibration curve generated from poly(styrene sulfonic acid) sodium salt polymer standards.

[0189] The polymer was stored as a solution at pH 3 at 4°C.

[0190] Example 4.1 Stability of 15% DM and 65 kDa HA-SH

[0191] The results of HA-SH with 15% DM are shown in Table 4.

[0192] Table 4 Molecular weight of HA-SH over a period of time

[0193]

[0194]

[0195] Surprisingly, although the storage conditions of HA-SH in solution form were similar to those in Example 3, it can be seen from Table 4 that HA-SH with a lower intrinsic viscosity was stable as a solution for at least 60 days. After about 90 days, the MW increased only slightly. Figure 6 shows an example of the MW change trend of the polymers in Table 4 and the original GPS curve.

[0196] Example 4.2 Stability of 25% DM and 65 kDa HA-SH.

[0197] Example 4.1 showed that SH polymers were exceptionally stable in solution only by modifying low [η] polymers. We further investigated whether SH polymers with higher DM (10.16 mg / mL) could be stabilized in solution at 4°C.

[0198] Table 5 Molecular weight of HA-SH over a period of time

[0199]

[0200]

[0201] Table 5 shows an example of the stability of 65 kDa HA-SH with 25% Dm. The results show that the molecular weight of HA-SH is stable for at least 70 days. Figure 7 shows an example of the MW variation trend of the polymers in Table 5 and the original GPS curve.

[0202] Example 4.3 Stability of 45 kDa Dextran-SH at approximately 5% and 12.5% ​​DM.

[0203] To further demonstrate the stability of SH polymers with low [η], about 45 kDa dextran was modified to dextran-SH according to Example 2. Take DM of 5% and 12.5% ​​dextran-SH as an example. It should be noted that dextran is a polymer composed of monosaccharide repeating units, and the molecular weight of the repeating unit is about 160Da, while the molecular weight of the disaccharide repeating unit of HA is about 400Da. Therefore, 5% and 12.5% ​​DM dextran-SH have similar SH densities to 12% and 30% DM HA-SH.

[0204] The results of the study are shown in Table 6. It was found that the molecular weight of both polymers did not increase for at least 180 days. FIG8 shows an example of the MW variation trend and the original GPS curve of the polymers in Table 6.

[0205] Table 6 Molecular weight of dextran-SH over a period of time

[0206]

[0207]

[0208] 4.4 Stability of 16.4% DM and 670 kDa HA-SH.

[0209] We further investigated whether a polymer of HA-SH with a slightly higher molecular weight and intrinsic viscosity of 670 kDa and [η] = 1156 ml / g is stable in solution (5.5 mg / mL) at 4° C. In this example, the DM of the polymer is 16.4%.

[0210] HA-SH was stored in a dilute HCl solution at pH 3. We found that the polymer was stable on day 1 after purification. After 7 days, the polymer was still mostly uncrosslinked, although some higher molecular weight fractions could be seen. At 14 days, higher molecular weight polymers could be seen in the AGE (indicated by arrows). At 30 days, the polymer formed a gel on its own, indicating significant self-crosslinking. Results ( Fig.13 ) showed that the material was relatively stable compared with HA-SH at 2.6 MDa.

[0211] Example 5 Formation of hydrogels from modified high [η] polymers and modified low [η] polymers

[0212] HA-VS, HA-SH and dextran-SH are prepared according to Example 2. First, the concentration of HA-VS and HA-SH or dextran-SH is determined. A known volume of polymer solution is freeze-dried and the dry weight of the polymer is measured. The dried polymer is at least 4 mg to ensure accurate measurement. Alternatively, the polymer concentration of HA-VS and HA-SH is measured by the previously described CTAB assay (Oueslati et al., "CTAB turbidimetric method for assaying hyaluronic acid in complex environments and under cross-linked form, Carbohydrate Polymers, 2014), and the polymer concentration of dextran-SH is measured by polarimeter according to the Chinese Pharmacopoeia. Then the known concentrations of HA-VS and HA-SH or dextran-SH are adjusted to pH 7.4 by adding 0.5M PB. The final concentration of PB is about 0.02M to 0.05M. The osmotic pressure is then adjusted with 25% NaCl. The polymers were then mixed at different target volume and mass ratios and adjusted to the target final concentration by adding phosphate buffered saline (PBS).

[0213] The polymer was incubated at 37°C for 24 hours to form a hydrogel. The hydrogel formation reaction was as follows Figure 3 As shown. After the incubation period, the hydrogels were first visually inspected for gel formation with the help of careful pipetting. For those conditions that successfully formed a gel-like structure, the formed hydrogel was loaded onto the lower plate of the 60 mm cone and plate fixture (CP60-1 / T1) of the Anton Paar rheometer and the mechanical properties (e.g., G' and G") were measured. Higher G' values ​​compared to the G" values ​​in the linear viscoelastic region (LVR) (e.g., G'>G") were used as an objective indicator of hydrogel formation.

[0214] 5.1 Hydrogels formed by different polymer concentrations

[0215] As a demonstration of principle, a large [η] polymer (HA-VS of 2.6 MDa at 23% DM, [η] = 2960 ml / g) was mixed with a small [η] polymer (HA-SH of 65 kDa at 14% DM, [η] = 106 ml / g) as follows:

[0216] Group 1: 0.64 mg / ml of HA-SH and 1.01 mg / ml, 0.81 mg / ml, 0.65 mg / ml, 0.52 mg / ml, 0.42 mg / ml, and 0.33 mg / ml of HA-VS.

[0217] Group 2: 0.43 mg / ml of HA-SH and 1.01 mg / ml, 0.81 mg / ml, 0.65 mg / ml, 0.52 mg / ml, 0.42 mg / ml, and 0.33 mg / ml of HA-VS respectively.

[0218] Group 3: 0.34 mg / ml of HA-SH and 1.27 mg / ml, 1.01 mg / ml, 0.81 mg / ml, 0.65 mg / ml, 0.52 mg / ml, and 0.41 mg / ml of HA-VS respectively.

[0219] Group 4: 0.28 mg / ml of HA-SH and 1.27 mg / ml, 1.01 mg / ml, 0.81 mg / ml, 0.65 mg / ml, 0.52 mg / ml, and 0.41 mg / ml of HA-VS respectively.

[0220] G' and G" (n=3 for each formulation) measured at 5 rad / s frequency and 5% strain are shown in Tables 7-10. Figure 9-10The trends of G' for different formulations are shown. These results indicate that if the HA-VS concentration is held constant, the mechanical properties decrease as the HA-SH concentration decreases. If the HA-SH is held constant, the mechanical properties decrease as the HA-VS concentration decreases. The ideal value of G' can be adjusted by adjusting the concentrations of the two gel-forming polymers. When the concentration of HA-VS is below its overlap concentration (c*), or about 0.33 mg / ml, no gel is formed. The overlap concentration can be calculated as follows:

[0221] c*=1 / [η].

[0222] Table 7 Gel formation of HA-SH 65kDa 14% DM at 0.64 mg / ml

[0223]

[0224] Table 8 Gel formation of HA-SH 65kDa 14% DM at 0.34mg / ml

[0225]

[0226]

[0227] Table 9 Gel formation of HA-SH 65kDa 14% DM at 0.43 mg / ml

[0228] HA-VS concentration (mg / ml) HA-VS:HA-SH molar ratio G'(Pa) SD(Pa) G”(Pa) SD(Pa) 1.01 1:10.7 0.999 0.004 0.229 0.003 0.81 1:13.5 0.611 0.001 0.134 0.002 0.65 1:16.8 0.346 0.002 0.107 0.002 0.52 1:20.9 0.165 0.002 0.070 0.002 0.42 1:26.2 0.057 0.002 0.041 0.001 0.33 1:32.4 No gel

[0229] Table 10 Gel formation of HA-SH 65kDa 14% DM at 0.28mg / ml

[0230] HA-VS concentration (mg / ml) HA-VS:HA-SH molar ratio G'(Pa) SD(Pa) G”(Pa) SD(Pa) 1.27 1:8.8 0.649 0.002 0.293 0.003 1.01 1:11.1 0.428 0.002 0.189 0.002 0.81 1:13.8 0.281 0.002 0.134 0.002 0.65 1:17.2 0.152 0.002 0.094 0.001 0.52 1:21.5 0.060 0.002 0.056 0.002 0.41 1:26.7 No gel

[0231] Another hydrogel was formed by using a large [η] polymer (HA-VS of 2.6 MDa at 23% DM, [η] = 2960 ml / g) and mixed with a low molecular weight small [η] polymer (HA-SH of 670 kDa at 16.4% DM, prepared as in Example 2.2, [η] = 1156 ml / g). A hydrogel was formed for a mixture of 0.8 mg / ml HA-VS and 0.4 mg / ml HA-SH (molar ratio between HA-VS and HA-SH was 1:1.9).

[0232] Another hydrogel was formed by using a large [η] polymer (HA-VS of 670 kDa, prepared as in Example 2.1, [η] = 1156 ml / g) and mixed with a low molecular weight small [η] polymer (HA-SH of 65 kDa, prepared as in Example 2.2, [η] = 106 ml / g). In this example, the concentration of HA-VS was 2.5 mg / ml and the DM was 40%. The concentration of HA-SH was 0.42 mg / ml and the DM was 14.3%. The molar ratio between HA-VS and HA-SH was 1:1.7. At 5% strain and 1 rad / s, G' is 0.96 Pa and G" is 0.38 Pa. In another embodiment, the concentration of HA-VS is 4 mg / ml and the DM is 40%. The concentration of HA-SH is 0.08 mg / ml and the DM is 14.3%. The molar ratio between HA-VS and HA-SH is 4.9:1. No gel is formed. In another embodiment, the concentration of HA-VS is 4 mg / ml and the DM is 40%. The concentration of HA-SH is 0.16 mg / ml and the DM is 14.3%. The molar ratio between HA-VS and HA-SH is 2.4:1. The mechanical properties of this gel are shown in Table 11.

[0233] Table 11 Mechanical properties of gel

[0234]

[0235] 5.2 Hydrogels formed by polymers with different DM

[0236] The DM of small [η] polymers can be varied and hydrogels can be formed. Fig.11 Shown are G' values ​​for hydrogels made by mixing 2.6 MDa HA-VS at 23% DM and 65 kDa HA-SH at 14% or 22% DM at 1 mg / ml. The values ​​were measured with a frequency of 5 rad / s and a strain of 5%. The formulation ranges are as follows:

[0237] Group 1: HA-SH at 14% DM, and about 0.14 mg / ml to about 0.3 mg / ml of HA-SH.

[0238] Group 2: 22% DM of HA-SH, and about 0.14 mg / ml to about 0.3 mg / ml of HA-SH. Results ( Fig.11 ) showed that when HA-VS was kept constant, the mechanical strength of the hydrogel decreased when the concentration and DM of HA-SH decreased. Therefore, the ideal value of G' can be adjusted by adjusting the DM and concentration of the hydrogel-forming polymer.

[0239] 5.3 Hydrogels formed from dextran-SH

[0240] Another small [η] polymer, 45 kDa (or [η] = 20 ml / g) dextran-SH was used as another example. Table 12 and Fig.12 G' is shown for different formulations consisting of a large [η] polymer (HA-VS of 2.6 MDa at 23% DM, [η] = 2960 ml / g) and dextran-SH of 45 kDa (or [η] = 20 ml / g) at 13% and 5% DM. The formulation ranges are as follows:

[0241] Group 1: 0.81 mg / ml of HA-VS, 13% DM and about 0.1 mg / ml to about 0.35 mg / ml of dextran-SH, respectively.

[0242] Group 2: 0.81 mg / ml of HA-VS, and 5% DM and about 0.1 mg / ml to about 0.35 mg / ml of dextran-SH, respectively.

[0243] Group 3: 0.65 mg / ml of HA-VS, 13% DM and about 0.1 mg / ml to about 0.35 mg / ml of dextran-SH, respectively.

[0244] Group 4: 0.65 mg / ml of HA-VS, 5% DM and about 0.1 mg / ml to about 0.35 mg / ml of dextran-SH, respectively.

[0245] The G' and G" values ​​at a frequency of 5 rad / s and a strain of 5% are shown. These results indicate that the mechanical strength decreases with decreasing HA-VS concentration, decreases with decreasing degree of dextran-SH (Dex-SH) modification, and decreases with decreasing dextran-SH concentration. The ideal value of G' can be tuned by adjusting the DM and concentration of the hydrogel-forming polymer.

[0246] Table 12 Mechanical properties of gel

[0247]

[0248]

[0249] 5.4 Hydrogels formed by PEG-SH

[0250] Another hydrogel was formed by using a large [η] polymer (2.6 MD HA-VS, prepared as in Example 2.1, [η] = 2960 ml / g) and mixed with a small [η] PEG-thiol (PEG-SH).

[0251] Another hydrogel was formed by using a large [η] polymer (HA-VS of 2.6 MD, prepared as in Example 2.1, [η] = 2960 ml / g) and mixed with a small [η] four-arm PEG thiol (5 KDa, [η] ~ 10 ml / g, obtained from commercial purchase). In this example, HA-VS was maintained at 0.8 mg / ml, and PEG dithiol was 0.4 mg / ml (sample 1), 0.2 mg / ml (sample 2) and 0.1 mg / ml (sample 3). Examples of mechanical properties measured at 5% strain are shown in Table 13:

[0252] Table 13 Mechanical properties of gel

[0253]

[0254] Example 6 Measurement of Mechanical Properties of Hydrogels Formed from Modified High [η] Polymers and Modified Low [η] Polymers HA-VS, HA-SH and dextran-SH were prepared according to Example 2. Hydrogels were formed and loaded into a rheometer according to Example 5. For illustrative purposes, four representative hydrogel formulations as shown in Table 14 are shown as examples. For F1 to F4, the molar ratio of HA-VS to SH polymer was 1:62, 1:12, 1:10, 1:16, respectively.

[0255] Table 14 Hydrogel formulation

[0256]

[0257] The mechanical properties of the hydrogels were measured under different types of mechanical testing modes. Examples of the tests are shown in Figures 14 to 17.

[0258] Fig.14A and Fig. 14B shows the results of a frequency sweep test. In this test, the oscillation strain was maintained at 5% and mechanical properties such as G' and G". were measured at different oscillation frequencies. This test showed that despite the very low G' values, the hydrogel is a viscoelastic solid rather than a viscous liquid because G' is higher than G" even at low frequencies.

[0259] Fig.15A and Fig. 15B Results of a strain sweep test are shown. In this test, the oscillation frequency was maintained at 5 rad / s and mechanical properties, such as G' and G", were measured at different oscillating strains. This test demonstrated the linear viscoelastic range (LVR) of the hydrogel. For hydrogels with similar G' at low shear strains (e.g., 1% for F2 and F4), they may behave differently at high strains (e.g., 100%). F2 was significantly less elastic than F4 (e.g., G'~G"). The results show that the elastic behavior under different strains is adjustable.

[0260] Fig.16A and Fig. 16B The results of the step stress test are shown. In the step stress test, a constant stress is applied to the material and the resulting strain is measured. In this test, we first applied a constant stress for 60 seconds, followed by 0Pa (relaxation) for 30 seconds. After that, a second constant stress was applied and then relaxed again. Four stresses, 0.05Pa, 0.1Pa, 0.2Pa and 0.5Pa, were gradually applied to the hydrogel. The results show that the material is indeed a viscoelastic solid under low stress conditions, because the strain of the material remains almost constant under each stress. If the material is a viscous solution, the strain response is expected to increase at a constant rate under each applied stress. Another evidence showing the solid properties of the hydrogel under low stress is that when the stress is removed (relaxation), the hydrogel more or less returns to the initial position with an elastic loop, similar to the bouncing motion of a spring after the load is removed instantly. In our embodiment, most hydrogels are relatively more elastic at low stress levels (strain is more constant, relaxation is more prominent), but relatively more viscous at higher stress levels (strain increases, relaxation is less prominent). A hydrogel with high elasticity at low stress does not necessarily correspond to high elasticity at high stress. For example, compared to the other hydrogels, F1 is more elastic at 0.05 Pa (e.g., strain is only 10%), but more viscous at 0.5 Pa (e.g., higher strain rate).

[0261] Fig.17A and Fig. 17B is the result of a continuous shear test. In this test, the shear viscosity of the material is measured at different shear rates. The results show that as the shear rate increases, the viscosity of the hydrogel decreases. For most hydrogels, the shear viscosity at a low shear rate (e.g., 0.1 / s) is at least 1000mPa·s, while the shear viscosity at a high shear rate (e.g., 1000 / s) is less than 100mPa. Accordingly, the viscosities of F1, F2, F3, and F4 at 0.1 / s are approximately 4200mPa·s, 1400mPa·s, 8100mPa·s, and 2100mPa·s. Accordingly, the viscosities of F1, F2, F3, and F4 at 1000 / s are approximately 9mPa·s, 23mPa·s, 32mPa·s, and 30mPa·s. Some hydrogels have higher viscosities at low shear rates, but lower viscosities at high shear rates, such as comparing F1 with F2.

[0262] Example 7 Synthesis of maleimide-modified hyaluronic acid (HA-MI)

[0263] Hyaluronic acid (HA) with a molecular weight of 2.6 MDa was obtained from Bloomage Freda (Jinan, China).

[0264] N-(2-Aminoethyl)maleimide trifluoroacetic acid (MI) and 4-(4,6-dimethoxy-1,3,5-triazin-2-yl)-4-methylmorpholine hydrochloride (DMTMM) were obtained from Aladdin Biotechnology.

[0265] MI molecules (15.10 mg) were added to a solution of HA (24 mg) in 8 ml of 1 mM PB. About 350 μl of 0.1 M NaOH was then added to the mixture to adjust the pH to 6.0, followed by the addition of DMTMM (66.4 mg). The molar ratio of -COOH in HA to -NH2 in MI to DMTMM was 1:1:4. After adding 320 μL of 25% NaCl, the reaction was stopped within 72 hours by precipitation in 32 mL of ethanol in a 50 mL conical tube. The precipitate was separated by centrifugation at 8000 rpm for 5 minutes and decanting the supernatant. The residual precipitate was redissolved in 10 mL of DI and further purified by dialysis in 4 L of DI for three days. The dialysis buffer was changed twice a day. The concentration of HA-MI in DI after dialysis was 1.6 mg / ml and DM was 4.8%.

[0266] Example 8 Formation of hydrogel from HA-MI

[0267] HA-MI prepared in Example 7 was mixed with HA-SH of 65 kDa and 11.6% DM in phosphate buffer. The final concentration was 1.1 mg / ml HA-MI, 1 mg / ml HA-SH in 0.02 M phosphate buffered saline at about 300 mOsm. A hydrogel was formed.

[0268] Example 9 Encapsulation of Active Pharmaceutical Ingredients (API) in Hydrogels

[0269] HA-VS, HA-SH and dextran-SH were prepared according to Example 2. Hydrogels were formed similarly to Example 5, except that the API in powder form was added to the polymer mixture before the hydrogel was formed. Nineteen representative hydrogel formulations are shown in Table 15 for illustrative purposes. The mechanical properties of four representative formulations measured according to Example 5 are shown in Table 16.

[0270] Table 15 Hydrogel formulation

[0271]

[0272]

[0273] Table 16 Mechanical properties of hydrogels

[0274] Hydrogel G'(Pa) G”(Pa) A15 0.17 0.06 A16 0.17 0.05 A17 0.21 0.06 A18 0.12 0.05

[0275] Example 10 Release of API from Hydrogel

[0276] Moxifloxacin was obtained from Hetero Drugs Limited. Levofloxacin was obtained from Aladdin Biotechnology. Bevacizumab was obtained from Roche. Improved RNA aptamers were obtained from Synbio Tech Inc.

[0277] 10.1 Release of Moxifloxacin

[0278] The following formulation (Table 17) was used to form a hydrogel with moxifloxacin.

[0279] Table 17 Formulation of hydrogel with moxifloxacin

[0280]

[0281] The hydrogel was formed according to Example 5. The gel was incubated at 37°C for 2 days before the release experiment. For the release experiment, a small portion of the gel (200-300 μg) was transferred to a 5 ml Eppendorf tube by a 3 mL disposable plastic pipette at ambient temperature. The mass of the gel was measured for the final release calculation. The Eppendorf tube was then slowly filled with 5 ml of PBS solution to minimize interference with the gel. The release experiment was performed at 37°C. At each predetermined time point (0.1 hour, 1 hour and 2 hours in this case), the test tube was gently shaken for 10 seconds and allowed to stand at ambient temperature for 10 minutes, and then 100 μl of release buffer was taken for high performance liquid chromatography (HPLC) quantification. Before injection, the release buffer was diluted 10 times with 0.1 M PB and filtered through a 0.22 μm syringe filter. HPLC was performed at a flow rate of 1.0 ml / min at 37°C using a mobile phase consisting of 0.05 M dipotassium phosphate / acetonitrile (82 / 18, v / v, pH=3). The eluate was passed through a YMC-Park Pro C18 column (4.6 mm×150 mm, 3 μm), and the detection wavelength was 293 nm. Moxifloxacin was used as a standard to measure the concentration, and the linear range was 2, 5, 10, 25, 50, 100 μg / ml. The experiment was performed in triplicate. Fig.18 Moxifloxacin was shown to be released rapidly and last for about 2 hours.

[0282] 10.2 Release of Levofloxacin

[0283] The following formula (Table 18) was used to form a hydrogel with levofloxacin. The hydrogel with levofloxacin was prepared according to 10.1. Levofloxacin was used as a standard to measure the concentration, and the linear range was 2, 5, 10, 25, 50, 100 μg / ml. Fig.19 Levofloxacin was shown to be released rapidly and last for about 2 hours.

[0284] Table 18 Formulation of hydrogel with levofloxacin

[0285]

[0286] 10.3 Release of IgG Protein

[0287] The following formulation (Table 19) was used to form a hydrogel with the protein drug bevacizumab.

[0288] Table 19 Formulation of hydrogel with bevacizumab

[0289]

[0290] Hydrogels were formed similarly to Example 5. Bevacizumab was used as an example of a protein drug. 200 μl of Avastin (purchased from Roche, USA) containing 25 mg / ml bevacizumab was mixed with 926 μl of 1.62 mg / ml HA-VS and 40.5 μl of 12.4 mg / ml HA-SH, 200 μl of 0.5 M phosphate buffer and an appropriate amount of double deionized water to obtain the final formulation according to Table 18. Before the release experiment, the gel was incubated at 37°C for 2 days. For the release experiment, a small portion of the gel (200-330 μg) was transferred to a 10 ml glass vial at ambient temperature by a 3 mL disposable plastic pipette, and the mass was measured for final release calculation. The glass vial was slowly filled with 8 ml of release buffer (PBS solution containing 40 mM arginine, pH adjusted to 7.4) to minimize interference with the gel. Release was performed at 37°C. At each predetermined time point (in this case 0.5 hours, 1 hour, 3 hours, 4.5 hours, 24 hours and 72 hours), the sample was gently shaken for 10 seconds and allowed to stand at ambient temperature for 10 minutes, and then 400 μl of release buffer was taken for HPLC quantification. Before injection, the release buffer was filtered through a 0.22 μm syringe filter. HPLC was performed at a flow rate of 0.5 ml / min at 30°C using a phosphate buffer consisting of 0.2 M potassium phosphate and 0.25 M potassium chloride (pH = 6.2). The eluent with an injection volume of 50 μl flowed through a Vanguard Cartridges Holder column and a Waters Xbridge Protein BEH SEC column (7.8 mm × 300 mm, 200A, 3.5 μm) in sequence, and the detection wavelength was 280 nm. Bevacizumab was used as a standard to measure the concentration, and the linear range was 12.5, 25, 50, 100 μg / ml. The experiment was performed in triplicate. Fig. 20 Bevacizumab was shown to be rapidly released within about 5 hours and to be continuously released for about 1-3 days.

[0291] 10.4 Aptamer Release

[0292] The following formulation (Table 20) was used to form a hydrogel with RNA-based aptamers.

[0293] Table 20 Formulation of hydrogel with aptamer

[0294]

[0295] A hydrogel was formed similarly to Example 5. An aptamer having the following nucleotide sequence and functional groups similar to Macugen was used as an aptamer example: CfGmGmAAUfCfAmGmUfGmAmAmUfGmCfUfUfAmUfAmCfAmUfCfCfGm3' (SEQ ID NO: 1), the 5' end was capped with 6 carbons (C6), and the 3' end was capped with 3'-dT-5' and Cy3 fluorescent dye. Gm or Am and Cf or Uf represent 2-methoxy and 2-fluoro variants of their respective purines and pyrimidines, and C, A, U and G encode cytidylic acid, adenylic acid, uridylic acid and guanylic acid. A hydrogel was formed similarly to Example 5, except that the solution before gel formation was added to the API in powder form. The gel was incubated at 37° C. for 2 days before the release experiment. For release experiments, a small portion of the gel (200-300 μg) was transferred to a 10 ml glass vial at ambient temperature by a 3 mL disposable plastic pipette and the mass was measured for final release calculations. The glass vial was slowly filled with 5 ml of PBS solution to minimize interference with the gel. Release was performed in triplicate at 37°C. At each predetermined time point (0.5 hour, 1 hour, 2 hours, and 4 hours in this case), the sample was gently shaken for 10 seconds and allowed to stand at ambient temperature for 10 minutes, then 1000 μl of release buffer was taken for UV quantification at 260 nm. The experiment was performed in triplicate. Fig.21 and Fig. 22 The aptamer was shown to be rapidly released from the hydrogel and lasted for about 4 h.

[0296] Although preferred embodiments of the present invention have been shown and described herein, it will be apparent to those skilled in the art that these embodiments are provided as examples only. The present invention is not intended to be limited by the specific examples provided in the specification. Although the present invention has been described with reference to the foregoing description, the description and illustration of the embodiments herein are not meant to be interpreted as having a limiting meaning. Without departing from the present invention, those skilled in the art will now be able to think of many variations, changes and replacements. In addition, it should be understood that all aspects of the present invention are not limited to the specific description, configuration or relative proportions set forth herein, which depend on various conditions and variables. It should be understood that various alternatives to the embodiments of the present invention described herein can be adopted when implementing the present invention. It is therefore contemplated that the present invention should also encompass any such substitutions, modifications, variations or equivalents. The following claims are intended to define the scope of the present invention, and methods and structures within the scope of these claims and their equivalents are thus encompassed. Sequence Listing <110> Shenzhen KeNeng Biopharmaceutical Co., Ltd. <120> Biocompatible materials and methods of preparation and use thereof <130> 0013-PA-013CN <160> 1 <170> PatentIn version 3.5 <210> 1 <211> 27 <212> RNA <213> Artificial Sequence <220> <223> aptamer <220> <221> c <222> (1)..(1) <223> c represents 2-fluoro variant of cytidylic acid <220> <221> g <222> (2)..(2) <223> g represents 2-methoxy variant of guanylic acid <220> <221> g <222> (3)..(3) <223> g represents 2-methoxy variant of guanylic acid <220> <221> u <222> (6)..(6) <223> u represents 2-fluoro variant of uridylic acid <220> <221> c <222> (7)..(7) <223> c represents 2-fluoro variant of cytidylic acid <220> <221> a <222> (8)..(8) <223> a represents 2-methoxy variant of adenylic acid <220> <221> g <222> (9)..(9) <223> g represents 2-methoxy variant of guanylic acid <220> <221> u <222> (10)..(10) <223> u represents 2-fluoro variant of uridylic acid <220> <221> g <222> (11)..(11) <223> g represents 2-methoxy variant of guanylic acid <220> <221> a <222> (12)..(12) <223> a represents 2-methoxy variant of adenylic acid <220> <221> a <222> (13)..(13) <223> a represents 2-methoxy variant of adenylic acid <220> <221> u <222> (14)..(14) <223> u represents 2-fluoro variant of uridylic acid <220> <221> g <222> (15)..(15) <223> g represents 2-methoxy variant of guanylic acid <220> <221> c <222> (16)..(16) <223> c represents 2-fluoro variant of cytidylic acid <220> <221> u <222> (17)..(17) <223> u represents 2-fluoro variant of uridylic acid <220> <221> u <222> (18)..(18) <223> u represents 2-fluoro variant of uridylic acid <220> <221> a <222> (19)..(19) <223> a represents 2-methoxy variant of adenylic acid <220> <221> u <222> (20)..(20) <223> u represents 2-fluoro variant of uridylic acid <220> <221> a <222> (21)..(21) <223> a represents 2-methoxy variant of adenylic acid <220> <221> c <222> (22)..(22) <223> c represents 2-fluoro variant of cytidylic acid <220> <221> a <222> (23)..(23) <223> a represents 2-methoxy variant of adenylic acid <220> <221> u <222> (24)..(24) <223> u represents 2-fluoro variant of uridylic acid <220> <221> c <222> (25)..(25) <223> c represents 2-fluoro variant of cytidylic acid <220> <221> c <222> (26)..(26) <223> c represents 2-fluoro variant of cytidylic acid <220> <221> g <222> (27)..(27) <223> g represents 2-methoxy variant of guanylic acid <400> 1 cggaaucagu gaaugcuuau acauccg 27

Claims

1. A composition comprising at least one first polymer having a first reactive group and at least one second polymer having a second reactive group, in, The first polymer has an intrinsic viscosity [η] of at least 500 ml / g, The second polymer has an intrinsic viscosity [η] lower than that of the first polymer and less than 1200 ml / g, and The concentration of the first polymer in the composition is at most 5 mg / ml, wherein the first polymer is capable of reacting with the second polymer to form a hydrogel.

2. The composition according to claim 1, wherein the first polymer and / or the second polymer is hydrophilic and / or water-soluble.

3. The composition of claim 1, wherein the first polymer and / or the second polymer are independently selected from the group consisting of polysaccharides, poly(acrylic acid), poly(hydroxyethyl methacrylate), elastin, collagen, polyethylene glycol, derivatives thereof, and any combination thereof.

4. The composition of claim 1, wherein the first polymer and / or the second polymer are independently selected from the group consisting of hyaluronic acid, guar gum, starch, chitosan, chondroitin sulfate, alginate, carboxymethylcellulose, dextran, derivatives thereof, and any combination thereof.

5. The composition according to claim 1, wherein the first polymer and / or the second polymer are independently selected from the group consisting of hyaluronic acid, dextran, derivatives thereof, and any combination thereof.

6. The composition of claim 1, wherein the first polymer comprises a first polymer derivative, the first polymer derivative comprises the first reactive group, and the first polymer derivative is electrophilic.

7. The composition of claim 6, wherein the first reactive group is selected from the group consisting of vinyl, acryl, thiol, olefin, thiol ester, isocyanate, isothiocyanate, alkyl halide, sulfonyl halide, epoxide, imido ester, fluorophenyl ester, carbonate, carbodiimide, disulfide, aziridine, and any combination thereof.

8. The composition of claim 6, wherein the first reactive group is selected from the group consisting of vinyl sulfone, maleimide, acrylate, methacrylate, epoxide, and any combination thereof.

9. The composition of claim 1, wherein the second polymer comprises a second polymer derivative, the second polymer derivative comprises the second reactive group, and the second polymer derivative is nucleophilic.

10. The composition of claim 9, wherein the second reactive group is selected from the group consisting of thiols, amines, azides, hydrazides, dienes, hydrazines, hydroxylamines, and any combination thereof.

11. The composition of claim 1, wherein the first polymer has a molecular weight of 500,000 to 5,500,000 Daltons.

12. The composition of claim 1, wherein the second polymer has a molecular weight of 3,000 to 800,000 Daltons.

13. The composition of claim 1, wherein the molecular weight (MW) ratio between the first polymer and the second polymer in the composition is from 500:1 to 1.5:

1. 14 . The composition of claim 1 , wherein a radius of gyration (Rg) ratio between the first polymer and the second polymer in the composition is from 150:1 to 1:

1. 15 . The composition according to claim 1 , wherein a mass ratio between the first polymer and the second polymer in the composition is 20:1 to 1:

20.

16. The composition of claim 1, wherein the molar ratio between the first polymer and the second polymer in the composition is 4:1 to 1:

500.

17. The composition of claim 1, wherein the first polymer has an intrinsic viscosity [η] of 500 ml / g to 5000 ml / g.

18. The composition of claim 1, wherein the second polymer has an intrinsic viscosity [η] of 5 ml / g to 1800 ml / g.

19. The composition of claim 1, wherein the ratio between the intrinsic viscosities of the first polymer and the second polymer in the composition is from 500:1 to 1:

1.

20. The composition of claim 6, wherein the derivative has an average degree of modification (DM) of 3% to 50%.

21. The composition of claim 6, wherein the first polymer derivative has a first DM, the second polymer derivative has a second DM, and a ratio between the first DM and the second DM is from 20:1 to 1:

20.

22. The composition of claim 6, wherein the first polymer derivative is a dextran derivative modified with one or more vinyl sulfone groups, a hyaluronic acid derivative modified with one or more vinyl sulfone groups, a hyaluronic acid derivative modified with one or more maleimide groups, or a combination thereof, and the second polymer derivative is a dextran derivative modified with one or more thiol groups, a hyaluronic acid derivative modified with one or more thiol groups, or a combination thereof.

23. The composition of claim 4, wherein the first polymer and / or the second polymer is contained in the composition in the form of a formed hydrogel.

24. The composition of claim 1, wherein the composition does not comprise any cross-linking agent different from the first polymer and / or the second polymer.

25. A hydrogel formed from the composition of any one of claims 1 to 24.

26. The hydrogel of claim 25 which is biocompatible.

27. The hydrogel according to any one of claims 25 to 26, having at least one of the following properties: 1) a storage modulus G' not exceeding 5 Pa, measured in a dynamic oscillatory shear test at 5 rad / s and 5% strain; and 2) Viscosity not exceeding 500 mPa·s, measured in a continuous shear test at a shear rate exceeding 1000 / s, 3) The loss modulus G” does not exceed 100% of its storage modulus G’, measured in a dynamic oscillatory shear test at 5 rad / s and 5% strain.

28. A method of producing a hydrogel, comprising: a) providing a composition according to any one of claims 1 to 24; and b) subjecting said composition to conditions capable of forming said hydrogel.

29. The method of claim 28, wherein the subjecting comprises incubating the composition at 15°C to 50°C.

30. A pharmaceutical composition comprising the hydrogel of any one of claims 25 to 27.

31. The pharmaceutical composition of claim 30, wherein the hydrogel is formulated to be suitable for drug encapsulation.

32. The pharmaceutical composition of claim 30, wherein the pharmaceutical composition comprises a drug, and the drug is encapsulated in the hydrogel.

Citation Information

Patent Citations

  • Polymer formulations for delivery of bioactive agents

    CN101677957A

  • Modified hyaluronic acid polymer compositions and related methods

    CN102573941A

  • Stabilized compositions comprising hyaluronic acid

    CN105026480A

  • Biocompatible material and methods for making and using thereof

    WO2019057035A1

  • Compositions and methods for controlled release of target agent

    WO2020015737A1